The Influence of Digital Financial Literacy on the Use of Non-Cash Payments in Makassar City: Gender as a Moderating Variable - Fera Fahira; Agusdiwana Suarni; Muhammad Khaedar Sahib (www.amertainstitute.com, 2024)
This study examines the influence of digital financial literacy on the adoption of non-cash payments among residents of Makassar City, using gender as a moderating variable. A total of 103 respondents were surveyed through explanatory and quantitative research methodologies. The analysis reveals that digital financial literacy positively and significantly affects the adoption of non-cash payments. However, the moderating effect of gender on this relationship is not statistically significant, as indicated by a p-value greater than 0.05. This suggests that digital financial literacy has a universally positive impact on the adoption of non-cash payments, irrespective of gender. The findings underscore the critical role of digital financial literacy in promoting non-cash payment systems, highlighting that its benefits extend equally across all gender groups. This aligns with broader efforts to create inclusive financial ecosystems and emphasizes the importance of fostering digital financial skills at all levels of society. The study calls for targeted initiatives to improve digital financial literacy through education programs, workshops, and outreach efforts, ensuring equitable access to digital financial tools. Future research could explore additional moderating variables, such as age, income, or education level, to gain a deeper understanding of the factors influencing non-cash payment adoption in urban contexts like Makassar City.